Pengaruh Penerapan Model Pembelajaran Sains Teknologi Masyarakat (STM) Terhadap Hasil Belajar Biologi Siswa Kelas X SMA Negeri 3 Boyolali Tahun Pelajaran 2012/2013 - WATI, ICHA KURNIA; KARYANTO, PUGUH; SANTOSA, SLAMET (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
The rapid development of science and technology in the 21st century requires students to think critically, creatively and highly a positive attitude towards science, society, and possess initiative correspond to issues resulted by the impact of science and technology’s application. Learning model that correspond to the development of science and technology is STS learning model, because the learning model allows students actively involved in learning and to show the role of science and technology in society. The aim of this research is to know the influence of STS learning model toward biology learning achievement of X degree students at SMA Negeri 3 Boyolali in 2012/2013 academic year. This research was a quasi experiment research using posttest only non equivalent group design. This research applied STS learning model towards experimental group upon class X at SMA Negeri 3 Boyolali in academic year 2012/2013. Cluster sampling was used upon the population. Data was collected using test and non test method, and analyzed by t-test. T-test results of the three domains is t count > t table so that Ho is rejected. This research concluded that the application of STS learning model has taken good effect toward student’s achievement cognitive, psychomotor, and  affective domain in learning biology of SMA Negeri 3 Boyolali.